PERBANDINGAN PERSEPSI AUDITOR INTERNAL, AKUNTAN PUBLIK, DAN AUDITOR PEMERINTAH TERHADAP PENUGASAN FRAUD AUDIT DAN PROFIL FRAUD AUDITOR - Eman Sukanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
The Fraud scheme that is happened in the government and commercial entity has a bad influence to the economic system and harmful to the stakeholders. A professional auditor as the locomotive to move good corporate governance and as a goalkeeper to prevent fraudulence has a great role to create a healthy and accountable economic system. Recent years, there are significant changes in the auditor profession. The change influenced by regulatory from foreignor domestic, directly or indirectly, demand higher requirement in the auditor’s work system.Internal auditor, public accountant, or government auditor relatively different inorganization structural, employment status, job assignment, and guidance used in the audit. However, their work is essentially the same, that is giving sufficient “ to plan and perform the audit to obtain reasonable assurance about whether the financial statements are free of material misstatement, whether caused by error or fraud” to plan and perform the audit to obtain , whether caused by error or fraud”. This study held to asses and analyze the perception ofinternal auditor, external auditor, and governmental auditor to the fraud audit and the profile of the fraud auditor when they conducted the examination duty.Sampling technique used the purposive sampling. There are 153 respondents, 33internal auditors work in business entity, 66 external auditors work in the Public Accountant Office and 54 government auditors work in BPK. To examine the hypothesis, this study used One Way Anova.The result that there is no different perception significantly between internal auditor, external auditor and government auditor to the Fraud Audit assignation and The Fraud Auditor profile. Averaged perceptions they have were high. This shows that the three groups of auditor all have strong willingness to prevent, detect, and investigate fraud.